Using sensorless direct torque with fuzzy proportional-integral controller to control three phase induction motor - Yaser Nabeel Ibrahem Alothman; Wisam Essmat Abdul-Lateef; Sabah Abdul-Hassan Gitaffa (Bulletin of Electrical Engineering and Informatics, 2023)
Induction motors (IM) attracted many researchers in the last few decades. In this field, various applications are implemented, such as servo motor drives and electric vehicles. This work applies a sensorless direct torque controller (DTC) to control a three-phase IM. System dynamics of the IM were derived. A nonlinear dynamic model had introduced with white noise. Given the complexity of the dynamics, the Jacobean Linearization technique has been used to obtain the linear model for a control task. A DTC technique is employed to control the motor speed of the system with a combination of two controllers. The fuzzy proportional-integral (PI) controllers are applied to obtain the reference torque based on an optimization process against the speed error raise. The optimizer is called grey wolf optimizer (GWO) and is implemented to achieve the centre values of the two output memberships for the fuzzy PI controllers. Then the extended Kalman filter (EKF) is used to evaluate the direct and quadratic components of the rotor flux and rotor speed from the observation of stator voltages and currents. The system is tested employing MATLAB simulation software and determines the targeted results. The outcomes are evaluated to improve the control performance.